Long-term follow-up of patients with congenital diaphragmatic hernia - Terry L Buchmiller; Nicole Cimbak (BMJ Publishing Group, 2024)
Neonates with congenital diaphragmatic hernia encounter a number of surgical and medical morbidities that persist into adulthood. As mortality improves for this population, these survivors warrant specialized follow-up for their unique disease-specific morbidities. Multidisciplinary congenital diaphragmatic hernia clinics are best positioned to address these complex long-term morbidities, provide long-term research outcomes, and help inform standardization of best practices in this cohort of patients. This review outlines long-term morbidities experienced by congenital diaphragmatic hernia survivors that can be addressed in a comprehensive follow-up clinic.